Meningkatkan Mutu Pendidikan Karakter Melalui Film â€œSokola Rimbaâ€ - Payuyasa, I Nyoman; Primayana, Kadek Hengki (LPM IHDN Denpasar, 2020)
Education serves to improve intellectual intelligence and human character. Character education must go through a learning process. The education process in the Covid-19 pandemic situation was forced to be carried out online. This situation will hamper the student's character learning process. Aside from being an entertainment, film becomes an educational media for the community. The film